Os serviços intensivos em conhecimento: um modelo de prestação de serviços aplicado no âmbito de serviços de baixa tecnologia - Costa, Regina Maria da (Universidade do Vale do Rio dos Sinos, 2017)
The main goal of this study was to describe the structure of an intensive knowledge transferring business provided by low technology and low clock speed suppliers. The background information used to support this study was obtained from “Service operations management”, Knowledge Intensive Business Services (KIBS), “Theoretical model of the service delivery process in KIBS” and “Forms of Quality Evaluation in Service Operations”. The analytical method employed in this study was qualitative, with a descriptive-exploratory bias, based on multiple cases. Data were collected using two semi-structured interview forms based on the service provider theoretical model. One of the forms was given to the service providers of the Administration, Agronomy and Accounting undergraduate courses of Mato Grosso State University (UNEMAT), in Tangará da Serra, a knowledge-intensive public institution. The second form was directed to farmers (family-based agriculture), businessmen and one representative of the female farmers association. A complementary instrument was also used as a resource for the performance evaluation of the providers under the costumers view. Data were analyzed through the content analysis technique, which allowed, at the beginning, to explore the seven phases of the reference theoretical model. After that, a cross analysis made possible to identify similar information and/or the identification of repeated information on the different forms, as well as the identification of specific situations of the study. Nowadays, the services provided by the university to the society are as follows: teaching, research and extension. However, the major efforts are directed towards teaching (B2C), being the provided service attributed to the organizations (B2B), by the means of extension projects, as a complement of the end-activity. The results showed that the emphasis used by the providers from UNEMAT and their respective clients for each stage of the service provided might differ from the perspective of a professional/client of traditional service, because the final objective is the financial benefit. However, the clients recognize the quality of the service provided, by the products or services created. As theoretical contributions of this research (i) suggests the alteration of the phase of supply of inputs for appointments and allocation of resources; (Ii) in phase VII that addresses the provider-customer relationship that aims to raise the factors that impact on the post-delivery relationship, understands that this phase is intrinsic in all other phases of the model and not only after service delivery. And (iii) with the elaboration of the complementary instrument directed to customers, it contributes significantly to the phase VI control and evaluation of the results of the service of the reference theoretical model. This study advanced theoretical discussions on Organizations and Competitiveness, especially on KIBS, helping several researchers to understand the concepts and importance of the organization of the several steps of the service providing process. The description of the model under the two contexts used in this study will allow future comparisons and relevant theoretical analysis.
Keywords: Operação de serviços; Processo; Baixa tecnologia; Baixo clockspeed; Casos múltiplos; Services operation; Process; Low technology; Low clockspeed; Multiple cases; ACCNPQ::Ciências Sociais Aplicadas::Administração